On the determinant of financial development in Africa: Geography, institutions and macroeconomic policy relevance - Ibrahim A. Adekunle; Olumuyiwa Ganiyu Yinusa; Tolulope O. Williams; Rahmon A. Folami (African Governance and Development Institute (AGDI), 2021)
While it is clear that financial depth and economic diversity are prerequisites for the realisation of growth and development objectives, heterogeneous factors that determines financial development remains imperfectly understood. This ambiguity in the structural relations between varied causative factors is more pronounced in Africa where conditions for growth and development remains inadequately met. Underexplored aspects such as geographic, political, economic and macroeconomic policy determinant of financial development in Africa could have culminated into the misalignment of the continent financialisation strategies. This paper takes the lead, diverse and holistic approach to assign numerical weights to these unobserved factors to reach conclusions that can redefine policy and research on Africa's financialisation objectives. We compared result along with the mean group (MG), common correlated effect mean group (CCEMG) and Augmented Mean Group (AMG) estimators but relied on the AMG results because of its high precision, relevance and superiority in addressing core issues of crosssectional dependence and slope homogeneity of regressors.Based on the AMG results, we found geographic, economic and macroeconomic policy factors to lead to financial development in Africa. However, our political/institutional composite index inversely relate to financial development in Africa. This counter-intuitive outcome could be due to Africa, age-long weak institutional capacities. Policy implications were discussed.
Keywords: D02; G20; P34; Q56; 330; Financial Development; Geography; Institutions; Macroeconomic Policy; Africa